2014
DOI: 10.1371/journal.pone.0105996
|View full text |Cite
|
Sign up to set email alerts
|

Visual Sensorial Impairments in Neurodevelopmental Disorders: Evidence for a Retinal Phenotype in Fragile X Syndrome

Abstract: Visual sensory impairments are common in Mental Deficiency (MD) and Autism Spectrum Disorder (ASD). These defects are linked to cerebral dysfunction in the visual cortical area characterized by the deregulation of axon growth/guidance and dendrite spine immaturity of neurons. However, visual perception had not been addressed, although the retina is part of the central nervous system with a common embryonic origin. Therefore, we investigated retinal perception, the first event of vision, in a murine model of MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 60 publications
12
57
0
Order By: Relevance
“…It would probably help us understand some distinguished behaviors that Fragile X Syndrome individuals present that may be caused by vision rather than cognition-related problems. It should also reinforce the hypothesis (Rossignol et al, 2014) that the overall “sensorial hypersensitivity” phenotype of Fragile X Syndrome is not only due to the well-known cerebral defects, but also to sensorial perception defects through the peripheral sensorial tissue.…”
Section: -Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…It would probably help us understand some distinguished behaviors that Fragile X Syndrome individuals present that may be caused by vision rather than cognition-related problems. It should also reinforce the hypothesis (Rossignol et al, 2014) that the overall “sensorial hypersensitivity” phenotype of Fragile X Syndrome is not only due to the well-known cerebral defects, but also to sensorial perception defects through the peripheral sensorial tissue.…”
Section: -Discussionsupporting
confidence: 52%
“…Such plasticity events have been described in the retina as well, and could account for modifications in retinal ganglion cell rectification currents (Jones et al, 2012). One recent paper has shown that FMRP is expressed in the retina and that its absence correlates with increases in the electroretinogram b-wave, which mostly reflects ON-bipolar cell depolarization to light (Rossignol et al, 2014). FMRP thus appears to influence retinal physiology.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 and 6) and since the sensitivity (k) and slope (n) of the a-wave intensity-response relation are unchanged in the VPA model. Such a decrease in the maximal amplitude with no concomitant change in the sensitivity or gain of the ERG a-wave was also described in the Fmr1 −/− mouse, an animal model with ASD-like behaviors that lacks the FMRP protein, among other retinal alterations [43,44], and points to the possibility that the phototransduction machinery within photoreceptors may be changed in the VPA model. Furthermore, since (i) the a-wave is contributed to by both rods and cones [30,34], (ii) rods contribute more to the ERG at low light levels, whereas cones contribute more at higher light levels [30,34], and (iii) our results show a larger effect at high light intensities, it is likely that cones are more affected than rods in VPA-exposed animals.…”
Section: Discussionmentioning
confidence: 60%
“…Thus, the over-expression of PINK1-AS could represent an oxidative stress induced signal reflecting the apoptotic status of treated RPE cells. In the meantime, the down-expression of both FMR1-IT1 and VIM-AS1, related to synaptogenesis, intracellular trafficking and cellular stability [104,105], could be seen as a final attempt of RPE cells to boost the production and sorting of vital proteins towards the most essential cellular districts. Additionally, nine miRNAs interacting with several down-regulated lncRNAs resulted involved in lysine degradation pathway.…”
Section: Discussionmentioning
confidence: 99%